Bridging The Gap Between Perceptions and Reality in Arabic Writing Proficiency Among Malaysian Higher Education Students: A Triangulation Approach - Mohamad Rofian Ismail; Azman Che Mat (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to assess Arabic writing proficiency among students at higher education institutions in Malaysia, focusing on their perceptions and actual performance through diagnostic testing. A descriptive-quantitative approach was employed, with instrument triangulation, including a questionnaire to evaluate students' perceptions and a diagnostic test to measure actual proficiency. The sample comprised 140 second-year students from four universities, selected through stratified random sampling. Findings revealed that students’ perceived ability was moderate, with an overall mean score of 3.44. Specific foundational skills, such as constructing simple sentences, were rated as high. However, the diagnostic test indicated a low level of writing proficiency, with an overall mean score of 2.34, highlighting a significant gap between students’ self-assessment and their actual performance. Further analysis identified weaknesses in syntax, idea cohesion, and paragraph development. The study underscores the need for a more holistic teaching approach, including intensive practical training, systematic guidance, and the integration of technology in Arabic language instruction. These findings provide valuable insights into students’ challenges and needs, serving as a foundation for developing more effective teaching and learning strategies.